Interview with Zaleha Kamaruddin - Yousif, Ahmed F (The International Institute of Islamic Thought, 2012)
This short article "Interview with Zaleha Kamaruddin" seeks to address her feelings, style, and role, as well the challenges in managing an international Islamic institution. It is based on her written answers to written questions, a recent unstructured interview, and personal contact gained while working together as administrators at IIUM during the 1990s.